Influence of Conductive Additives and Binder on the Impedance of Lithium-Ion Battery Electrodes: Effect of Morphology. Issue 1 (29th January 2020) - Hein, Simon; Danner, Timo; Westhoff, Daniel; Prifling, Benedikt; Scurtu, Rares; Kremer, Lea; Hoffmann, Alice; Hilger, André; Osenberg, Markus; Manke, Ingo; Wohlfahrt-Mehrens, Margret; Schmidt, Volker; et al.
Abstract : Most cathode materials for lithium-ion batteries exhibit a low electronic conductivity. Hence, a significant amount of conductive graphitic additives are introduced during electrode production. The mechanical stability and electronic connection of the electrode is enhanced by a mixed phase formed by the carbon and binder materials. However, this mixed phase, the carbon binder domain (CBD), hinders the transport of lithium ions through the electrolyte pore network. Thus, reducing the performance at higher currents. In this work we combine microstructure resolved simulations with impedance measurements on symmetrical cells to identify the influence of the CBD distribution. Microstructures of NMC622 electrodes are obtained through synchrotron X-ray tomography. Resolving the CBD using tomography techniques is challenging. Therefore, three different CBD distributions are incorporated via a structure generator. We present results of microstructure resolved impedance spectroscopy and lithiation simulations, which reproduce the experimental results of impedance spectroscopy and galvanostatic lithiation measurements, thus, providing a link between the spatial CBD distribution, electrode impedance, and half-cell performance. The results demonstrate the significance of the CBD distribution and enable predictive simulations for battery design. The accumulation of CBD at contact points between particles is identified as the most likely configuration in the electrodes under consideration.